The Antibacterial Activities of Some Thymus (Lamiaceae) Representatives Against Salmonella enteriditis Strain Locally Isolated - Honcharenko, Vitaliy; Tkachenko, Halyna; Nachychko, Viktor; Prokopiv, Andriy; Osadowski, Zbigniew (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2018)
Some of the plants of the Thymus genus were previously reported for their antimicrobial activities. Therefore, the aim of this study was to evaluate the antimicrobial effects of five ethanolic extracts obtained from leaves of some Thymus representatives (Thymus serpyllum L. emend. Mill., Th. pannonicus All., Th. × porcii Borbás, Th. pulegioides L., Th. alpestris Tausch ex A. Kern.) against Salmonella enteritidis strain. Freshly leaves were washed, weighted, crushed, and homogenized in 96 % ethanol (in proportion 1:19) at room temperature. The extracts were then filtered and investigated for their antimicrobial activity. Antimicrobial activity was determined using the agar disk diffusion assay. The ethanolic extract obtained from the leaves of Th. pulegioides was the most effective plant extracts against Salmonella enteritidis studied in this work. The antibacterial activity of extracts was greatest for Th. pulegioides followed by Th. pannonicus (13.1 ±0.85 mm) followed by Th. alpestris (12.6 ±0.25 mm), Th. x porcii (12.2 ±0.55 mm), and then by Th. serpyllum (10.5 ±0.23 mm). These plant extracts could be a potential source of new antibacterial agents. Further and more specific studies, in vivo, are recommended to determine the efficacy of these plants in the treatment of Salmonella-induced bacterial infections.